2021
DOI: 10.1096/fj.202101149r
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA‐sequencing atlas of bovine caudal intervertebral discs: Discovery of heterogeneous cell populations with distinct roles in homeostasis

Abstract: Back and neck pain are significant healthcare burdens that are commonly associated with pathologies of the intervertebral disc (IVD). The poor understanding of the cellular heterogeneity within the IVD makes it difficult to develop regenerative IVD therapies. To address this gap, we developed an atlas of bovine (Bos taurus) caudal IVDs using single-cell RNA-sequencing (scRNA-seq). Unsupervised clustering resolved 15 unique clusters, which we grouped into the following annotated partitions: nucleus pulposus (NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 118 publications
1
57
0
Order By: Relevance
“…Such classification is quite simple and may mask the deeper physiological functions and connections between tissues and cells. Recently, Several subgroups of AF and NP were further revealed by scRNA-Seq [ [56] , [57] , [58] , [59] ]. However, the biological function and significance of AF subgroups still need to be further discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Such classification is quite simple and may mask the deeper physiological functions and connections between tissues and cells. Recently, Several subgroups of AF and NP were further revealed by scRNA-Seq [ [56] , [57] , [58] , [59] ]. However, the biological function and significance of AF subgroups still need to be further discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Subcluster 1 was identified to be NP cells based on a relatively higher expression for Acan and Col2a1 while also expressing lower Col1a1 compared to other IVD cells [8,2932]. Additionally, these cells highly express Cd24 , a classical marker for NP cells [13,3335], previously identified markers of the chondrocyte lineage including S100B and a novel marker for bovine NP tissues, PDIA4 [19,36,37]. Cells mapping to the IAF cluster were similar in pattern of expression to that of NP cells, differing with modestly increased Col1a1 expression and decreased presence of Cd24 .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, single-cell RNA sequencing (scRNA-seq) of IVD cells, both from anatomically distinct regions and for comparisons with pathology, has been used to characterize the phenotype and abundance of distinct cell populations in the IVD in human and animal tissue sources [5,15,17,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, multiple bulk proteomics studies delineated the general cell heterogeneity of human IVD ( Rodrigues-Pinto et al., 2018 ; Tam et al., 2020b ) and made comparisons at different developmental stages ( Tam et al., 2020b ). Recent studies of single-cell atlases in nonhuman vertebrates resolved the cellular heterogeneity in bovine caudal IVD ( Panebianco et al., 2021 ) and found stem cells in rat IVD ( Wang et al., 2021 ). Another study provided single-cell analysis of human adult IVD that identified the NPC and AFC populations ( Fernandes et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%